2017
DOI: 10.1097/rlu.0000000000001759
|View full text |Cite
|
Sign up to set email alerts
|

Intense 99mTc-MDP Activity in an Elongated Sagging Gallbladder With a Partially Calcified Gallstone

Abstract: Intense activity was noted in the right middle abdomen on whole-body Tc-MDP bone scan images, which were obtained in a 78-year-old woman who had back pain. Further SPECT/CT images demonstrated that the intense activity was located in an elongated gallbladder. Partially calcified gallstone was also revealed on SPECT/CT images. Unexpectedly, the gallbladder activity was from the radioactive bile inside the gallbladder lumen, whereas the partially calcified gallstone was relatively photopenic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Notably, no PSMA uptake was observed in the gallbladder lumen. The incidental visualization of the gallbladder on nonhepatobiliary nuclear medicine studies has been reported in several cases, including 99m Tc-MDP scan, 2 111 In-pentetreotide scan, 3 and 68 Ga-PSMA-11 PET/CT scan 4 . In this case, increased PSMA uptake was observed in a gallbladder stone.…”
mentioning
confidence: 68%
“…Notably, no PSMA uptake was observed in the gallbladder lumen. The incidental visualization of the gallbladder on nonhepatobiliary nuclear medicine studies has been reported in several cases, including 99m Tc-MDP scan, 2 111 In-pentetreotide scan, 3 and 68 Ga-PSMA-11 PET/CT scan 4 . In this case, increased PSMA uptake was observed in a gallbladder stone.…”
mentioning
confidence: 68%